Detection of Common Copy Number of Variants Underlying Selection Pressure in Middle Eastern Horse Breeds Using Whole-Genome Sequence Data. (23rd May 2022) - Zandi, Mohammad Bagher; Salek Ardestani, Siavash; Vahedi, Seyed Milad; Mahboudi, Hossein; Mahboudi, Fereidoun; Meskoob, Ardeshir
Abstract: Dareshouri, Arabian, and Akhal-Teke are 3 Middle Eastern horse breeds that have been selected for endurance and adaptation to harsh climates. Deciphering the genetic characteristics of these horses by tracing selection footprints and copy number of variations will be helpful in improving our understanding of equine breeds' development and adaptation. For this purpose, we sequenced the whole genome of 4 Dareshouri horses using Illumina Hiseq panels and compared them with publicly available whole-genome sequences of Arabian ( n = 3) and Akhal-Teke ( n = 3) horses. Three tests of FLK, hapFLK, and pooled heterozygosity were applied using a sliding window (window size = 100 kb, step size = 50 kb) approach to detect putative selection signals. Copy number variation analysis was applied to investigate copy number of variants (CNVs), and the results were used to suggest selection signatures involving CNVs. Whole-genome sequencing demonstrated 8 837 950 single-nucleotide polymorphisms (SNPs) in autosomal chromosomes. We suggested 58 genes and 3 quantitative trait loci, including some related to horse gait, insect bite hypersensitivity, and withers height, based on selective signals detected by adjusted P -value of Mahalanobis distance based on the rank-based P -values (Md-rank-P) method. We proposed 12 genomic regions under selection pressure involving CNVs that were previously reported to be associated with metabolism energy ( SLC5A8 ), champagne dilution in horses ( SLC36A1 ), and synthesis of polyunsaturated fatty acids ( FAT2 ). Only 10 Middle Eastern horses were tested in this study; therefore, the conclusions are speculative. Our findings are useful to better understanding the evolution and adaptation of Middle Eastern horse breeds.